Financial literacy as a tool of business transformation for Small and Medium Enterprises in Uganda - Kibira, Vicent; Kiberu, Jonah; Twinamasiko, Emmanuel (Gateway Research Centre, 2021)
Majority of the businesses in developing countries, Uganda inclusive fall under Small and Medium Enterprises. They employ the largest part of the population and contribute to livelihood improvement and sustainability. SMEs thus play a significant role in economic growth and development of the economy. This brief presents what limits the performance of SMEs and recommends the possible policy measures that can be adopted to transform SMEs in Uganda citing financial literacy as the key general strategy to SME transformation. The limitations to SME growth highlighted include shortage of capital and credit facilities, limited skilled labor, inadequate raw materials, poor infrastructure, inefficient management skills, and the contained use of new, emerging, and constantly changing technologies.